2010
DOI: 10.4314/ejhd.v23i2.53227
|View full text |Cite
|
Sign up to set email alerts
|

Community case management improves use of treatment for childhood diarrhea, malaria and pneumonia in a remote district of Ethiopia

Abstract: Background: Ethiopia's Health Extension Workers (HEW) deliver preventive interventions and treat childhood diarrhea and malaria, but not pneumonia. Most of Ethiopia's annual estimated 4 million childhood pneumonia cases go untreated. Objective: Evaluate the performance of volunteers in providing Community Case Management (CCM) for diarrhea, fever and pneumonia-in a pre-HEW setting in Liben Woreda, Oromiya Regional State. Methods: Save the Children supported Ministry of Health and communities to deliver child s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 11 publications
1
20
0
Order By: Relevance
“…Other iCCM studies that reported on carers’ disease knowledge in Mali [40], Uganda [41], Ghana [23], Burkina Faso [23], Ethiopia [23, 42] and Malawi [23] also found similar results. Carers’ in Mali in the iCCM intervention arm were significantly more likely to recognise fever lasting more than one day after treatment and convulsions as danger signs than carers in the control group.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Other iCCM studies that reported on carers’ disease knowledge in Mali [40], Uganda [41], Ghana [23], Burkina Faso [23], Ethiopia [23, 42] and Malawi [23] also found similar results. Carers’ in Mali in the iCCM intervention arm were significantly more likely to recognise fever lasting more than one day after treatment and convulsions as danger signs than carers in the control group.…”
Section: Discussionsupporting
confidence: 65%
“…Carers in Kumasi (Ghana), Lilongwe (Malawi) and Ougadougou (Burkina Faso) improved their knowledge on signs of severe malaria but not those in Bolgatanga (Ghana) and Jimma (Ethiopia) [23]. A longer study (9 years) conducted in Ethiopia showed an increase in the recognition of fast and difficulty in breathing as signs of suspected pneumonia and other childhood danger signs [42]. The contribution of iCCM to prompt treatment seeking behaviour was also found in other studies in Ghana and in Uganda [19, 43, 44].…”
Section: Discussionmentioning
confidence: 99%
“…20 In a multi-methods Ethiopian study, volunteer CHWs treating diarrhoea, pneumonia, and fever and were highly accessed by community members 22 . Our study is complimentary suggesting multi-illness iCCM using CHWs with variable formal education is feasible, which is supportive of work in Eastern Uganda 23,[27][28][29][30] ; however, caution is needed to further understand quality of work, an issue highlighted by a recent study from Central Uganda.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 African iCCM studies are few, 14,18 and less still have assessed health outputs and outcomes. 5,14,[19][20][21][22][23] National programs in sub-Saharan Africa are new and while early studies are demonstrating implementation feasibility and early positive outcomes 7,8 , more studies are needed to understand implementation in a variety of contexts including use of volunteer CHWs with limited formal education and short iCCM training.…”
Section: Introductionmentioning
confidence: 99%
“…In Zambia, a CCM study on pneumonia and malaria found that 68% of children with pneumonia received early and appropriate treatment from community health workers, and that overtreatment of malaria significantly decreased 5. In Ethiopia, workers deployed in remote communities delivered two and a half times as many treatments for the three diseases than all the facility-based providers in the same district 18. The proportion of children receiving artemisinin-based combination therapy globally is also increasing, although significant gaps remain 14…”
Section: Justification For Integrated Ccmmentioning
confidence: 99%